Assessment of the reliability of serological monitoring results based on biobank materials - A. V. Nozdracheva; T. A. Semenenko (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate the safety of immunoglobulins (Ig) of different classes (IgA, IgM, IgG, IgE) under conditions of long-term low-temperature storage of blood serum samples.Material and methods. The work used samples of blood serum from the collection of the Department of Epidemiology, examined by enzyme immunoassay for antibodies of classes IgA, IgM, IgG, IgE twice as follows: immediately upon receipt in the laboratory and after storage at a temperature of -70о C for 8 years.Results. After the storage of seropositive sera, the level of IgA antibodies did not change significantly (p=0,7). For the remaining classes of immunoglobulins (IgM, IgG, IgE), a small (not >15%) but significant decrease (p<0,05), most pronounced for IgE, was observed. It was shown that the higher the antibody level in the samples during the first study, the more it decreased after long-term storage (correlation at p<0,05). This did not lead to false negative results, which is due to the greater accuracy in measuring small values.Conclusion. Long-term low-temperature storage of serum samples in biobank conditions ensures the safety of antibodies of different classes and is the basis for the reliability of future studies.